Analysis of Different Parameters Affecting Diffusion, Propagation and Survival of Staphylophages in Bacterial Biofilms - González, Silvia; Fernández, Lucía; Gutiérrez, Diana; Campelo, Ana Belén; Rodríguez, Ana; García, Pilar (Frontiers in Microbiology, 2018)
The elimination of bacterial biofilms remains a major challenge due to their recalcitrant nature. Bacteriophages, viruses that infect bacteria, have been gaining increasing attention as biofilm control agents. However, the development of a successful phage-based strategy requires in-depth analysis of different parameters. It is particularly important to determine the ability of a given phage to diffuse, propagate and remain viable within the complex biofilm structure. Here, we examine some of these properties for two staphylophages, vB_SauM_phiIPLA-RODI and vB_SepM_phiIPLA-C1C. Both Staphylococcus aureus and Staphylococcus epidermidis are important opportunistic pathogens that readily form biofilms on a wide array of biotic and abiotic surfaces. Our results confirmed that both phages could penetrate through biofilms formed by several bacterial strains with varying degrees of susceptibility to the viruses and biofilm-forming abilities. However, phage penetration differed depending on the specific bacterium or combination of bacteria. The data presented here suggest that the factors determining the diffusion rate of phages in biofilms include the amount of attached biomass, susceptibility of the strain, initial phage titer, phage entrapment in the extracellular matrix, and phage inactivation. This information will help to further characterize phage-bacteria interactions within biofilm communities and will be valuable for the development of antistaphylococcal products based on these phages.